A case of thoracic SMARCA4-deficient undifferentiated tumor located in Th5 paravertebral region - Iwai, Chizuo; (Iwata), Hidenori Kawamoto; Sasada, Yasuhiro; Akiyama, Haruhiko; Shirahashi, Koyo; Nozawa, Satoshi; Yamada, Kazunari; Iwata, Hisashi (Journal of Spine Research, 2024)
Introduction: SMARCA4-deficient undifferentiated tumours are characterised by a defect in the SMARCA4 gene, a new disease concept that was first reported in 2015.Case: A 58-year-old man presented with right chest pain. Chest CT presented a paravertebral tumour, and needle biopsy revealed it to be a SMARCA4-deficient undifferentiated tumour. The tumour was in the right paravertebral region of the fifth thoracic vertebra and extended through the right fifth or sixth intervertebral foramen into the spinal canal. A detailed resection plan was made preoperatively using VINCENT® medical image analysis software. First, a thoracoscopic resection was performed by a general thoracic surgeon. After the thoracoscopic procedure, Th4-5 hemi-laminoplasty and nerve root dissection were performed. The tumour on the lateral surface of the vertebral body was cauterised and en bloc resection was performed. Two years after surgery, the patient was doing well without recurrence.Conclusion: We report a rare case of a SMARCA4-deficient undifferentiated tumour of the thoracic region. En bloc resection was carefully planned using VINCENT® and surgical resection was performed, resulting in a good outcome.